Antimicrobial Stewardship in Surgery: A Literature Bibliometric Analysis - Liu, Yang-Xi; Yang, Ya; Le, Ke-Jia; Zhang, Zai-Li; Cui, Min; Zhong, Han; Gu, Zhi-Chun (Frontiers in Public Health, 2022)
Background: Antimicrobial resistance and the dwindling antibiotic development pipeline have resulted in a looming post-antibiotic era. Research related to antimicrobial stewardship (AMS) has grown rapidly in the past decade, especially in the field of surgery. We conducted a bibliometric analysis of these publications. In addition, we aimed to identify research hotspots and infer future research trends. Methods: We screened global publications on AMS in the surgical field over ten years (between 2011–2020) from the Web of Science core collection database. The keywords “antimicrobial or antibiotic”, “stewardship”, “management”, “management strategies”, “programme”, “surgery” and “surgical” were used to search for related papers. VOS viewer, R software, and other machine learning and visualization tools were used to conduct the bibliometric analysis of the publications. Results: We identified 674 publications on AMS in surgical fields; “antimicrobial stewardship” (with total link strength of 1096) was the most frequent keyword, and had strong links to “antimicrobial resistance” and “guidelines”. The top 100 most cited papers had a mean citation count of 47.21 (range: 17–1155) citations, which were cited by survey research studies, clinical trials, and observational studies. The highest-ranking and most cited journal was Clinical Infectious Diseases with eight publications. Jason G. Newland from Washington University wrote seven papers and was cited 1282 times. The University of Washington published 17 papers and was cited 1,258 times, with the largest number of publications by author and organization. The USA published 198 papers and cooperated with 21 countries, mainly partnering with Italy, the UK, and Canada. Published articles mainly focused on the current clinical situation regarding surgical AMS management, antibiotic prescription, and antibiotic resistance. Conclusions: Publications on surgical AMS management have increased in recent decades, with the USA being the most prolific. Epidemiological investigations of surgical-related infections, antibiotic prescriptions, and antibiotic resistance are fast-developing research trends. However, further improvements are still needed according to the recommendations gained from the bibliometric analysis.